Analisis Financial Leverage dan Asset Growth Terhadap Koefisien Respon Laba - Arna Suryani (Universitas Batanghari Jambi, 2021)
This purpose to analyze and find out how the influence of financial leverage and asset growth in earnings response coefficient. And uses quantitative methods from secondary data sourced from industrial company on the cosmetics & household goods sector in the Indonesian stock exchange period 2018-2020. This study sampel is selected based in on purposive addition certain criteria. Using multiple linear regression analysis performed classical assumption test, hypothesis test and coefficient of determination. The results of the study show that financial leverage has a positive and significant effect on the earnings response coefficient, while the asset growth variable has a positive but not significant effect on the earnings response coefficient. The results of this study prove that if financial leverage is high, then small changes in operating profit will greatly affect returns to shareholders. A large company size will find it easier to innovate by using its assets which will increase company profits. Investors will respond to high corporate profits by increasing the value of the earnings response coefficient.